Response Surface Methodology for Optimized Concentration of Gum Arabic, Maltodextrin, and Whey Protein Isolate in Arthrospira platensis Phycocyanin Microcapsules - Pebriyanti, Puspa; Budhiyanti, Siti Ari; Ekantari, Nurfitri (Faculty of Fisheries and Marine Universitas Airlangga, 2025)
Graphical Abstract Highlight Research Phycocyanin could be encapsulated by the spray-drying process with gum Arabic (GA), maltodextrin (MD), and whey protein isolate (WPI) as coating materials. The selected optimal formula for phycocyanin microcapsules consisted of 8.3% GA, 11.7% MD, and 5.2% WPI. The optimum formulation can produce phycocyanin microcapsules meeting 76.56% of the desired targets. The concentrations of three encapsulant ingredients (GA, MD, and WPI) influenced the resulting characteristics, e.g., phycocyanin content, antioxidant activity, encapsulation efficiency, phycocyanin retention, solubility, and particle size Abstract Phycocyanin is a blue-colored phycobiliprotein in Arthrospira platensis known for its antioxidant properties. Due to its sensitivity to pH, temperature, light, oxygen, and moisture, protecting phycocyanin pigments often involves microencapsulation through spray drying. This process allows the pigments to be rapidly entrapped within a wall material. The wall material for these microcapsules was composed of gum arabic, maltodextrin, and whey protein isolate. This study aimed to determine the optimal concentrations of these components to optimize encapsulation performance. Optimization was performed using the Minitab application with Response Surface Methodology (RSM) and a Central Composite Design (CCD). The independent variables were the concentrations of gum arabic, maltodextrin, and whey protein isolate, while the response variables measured included yield, phycocyanin content, antioxidant activity, encapsulation efficiency, phycocyanin retention, solubility, and particle size. Scanning electron microscopy (SEM) was used to analyze the morphology of the optimized microcapsules. The Minitab analysis recommended 20 potential optimization solutions, with the highest desirability value of 0.7656. The selected optimal formula consisted of 8.3% gum arabic, 11.7% maltodextrin, and 5.2% whey protein isolate. Predicted response values for this formulation were as follows: yield 75.30%, phycocyanin content 4.55%, antioxidant activity 48.87%, encapsulation efficiency 98.98%, phycocyanin retention 68.57%, solubility 95.15%, and particle size 212.73 nm. Validation results confirmed a yield of 81.70%, phycocyanin content of 3.56%, antioxidant activity of 52.08%, encapsulation efficiency of 93.96%, phycocyanin retention of 62.42%, and a particle size of 212.73 nm. These findings indicate that the proposed solution is both effective and acceptable.